Test and temperature field of finite element simulation about the effect of scanning speed on 304 stainless layer's properties by laser cladding. (November 2015) - Ju, H.; Xu, P.; Lin, C.; Sun, D.
Abstract : A 304 stainless layer was obtained by laser cladding on the surface of 45 steel using the way of pre-setting powder with the equipment of 5 kW transverse flow CO2 laser processing. Temperature field of 304 stainless layer in the laser cladding process was finite analysed by the software of ANSYS. The analysing process considered the heat source model the latent heat of phase change the unit of surface effect the mesh generation and the technology of element birth, etc. Effect of scanning speed on the dilution rate was analysed, and was compared with actual results. Then, results were analysed. The finite element analysis and result of experiment showed that the highest temperature the dilution rate and the width of the cladding laser were inversely proportional to the scanning speed of laser, and the height of cladding layer is in directly proportional to the scanning speed; the finite element analysis of temperature field sufficiently reflected the characteristic of rapid heating and cooling in the laser cladding process; the trend and numerical value of the dilution rate between experiments and finite element simulations about laser cladding 304 stainless steel are basically anastomosing.